Skin disorders of the trunk. II. - Bonifazi, E.; Ciampo, L.; Milano, A.; Ladisa, G.; Fronzi, S. (European Journal of Pediatric Dermatology, 2005)
Pityriasis lichenoides is a rare skin disorder -0.25% of all skin disorders- (2) with probable, but not confirmed virus etiology, with clinical course characterized by subintrant crops of lesions, spontaneously healing within months or years and clinically characterized in its more frequent variant or pityriasis lichenoides chronica (PLC) by purpuric papules (Fig. 1561) with typical clinical course. Its lesions exhibit a significant clinical variability that justifies the numerous names of the disorder. Its lesions really range from the papules of the more frequent chronic variant, which are completely asymptomatic, to the pustular, smallpox-like and necrotic lesions with sharp borders (Fig. 1562), associated to hyperpyrexia (pityriasis lichenoides et varioliformis acuta -PLEVA-). Between these two poles numerous intermediate forms do exist. Anyway, even in the hyperacute form the characteristic papules of the chronic variant can be seen. [...].